Consensus and variations in cell line specificity among human metapneumovirus strains - Nao, Naganori; Sato, Ko; Yamagishi, Junya; Tahara, Maino; Nakatsu, Yuichiro; Seki, Fumio; Katoh, Hiroshi; Ohnuma, Aiko; Shirogane, Yuta; Hayashi, Masahiro; Suzuki, Tamio; Kikuta, Hideaki; et al. (PloS one, 2019)
Human metapneumovirus (HMPV) has been a notable etiological agent of acute respiratory infection in humans, but it was not discovered until 2001, because HMPV replicates only in a limited number of cell lines and the cytopathic effect (CPE) is often mild. To promote the study of HMPV, several groups have generated green fluorescent protein (GFP)-expressing recombinant HMPV strains (HMPVGFP). However, the growing evidence has complicated the understanding of cell line specificity of HMPV, because it seems to vary notably among HMPV strains. In addition, unique A2b clade HMPV strains with a 180-nucleotide duplication in the G gene (HMPV A2b180nt-dup strains) have recently been detected. In this study, we re-evaluated and compared the cell line specificity of clinical isolates of HMPV strains, including the novel HMPV A2b180nt-dup strains, and six recombinant HMPVGFP strains, including the newly generated recombinant HMPV A2b180nt-dup strain, MG0256-EGFP. Our data demonstrate that VeroE6 and LLC-MK2 cells generally showed the highest infectivity with any clinical isolates and recombinant HMPVGFP strains. Other human-derived cell lines (BEAS-2B, A549, HEK293, MNT-1, and HeLa cells) showed certain levels of infectivity with HMPV, but these were significantly lower than those of VeroE6 and LLC-MK2 cells. Also, the infectivity in these suboptimal cell lines varied greatly among HMPV strains. The variations were not directly related to HMPV genotypes, cell lines used for isolation and propagation, specific genome mutations, or nucleotide duplications in the G gene. Thus, these variations in suboptimal cell lines are likely intrinsic to particular HMPV strains.